PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN DISIPILIN KERJA TERHADAP KEPUASAN KERJA PERANG KAT DESA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (Studi kasus Di Desa jetis, Desa Blimbing, Desa Widoropayung, Kecamatan Besuki, Kabupate - Karnadi, Karnadi; Anshory, Muhammad Iqbal; Toyyibah, Ni'matut (Fakultas Ekonomi dan Bisnis, 2024)
BUMDES is a village business managed by the village government, and is a legal entity. The purpose of this study was to analyze the effect of Leadership Style, Work Environment, and Work Discipline on Work Motivation with Job Satisfaction as an intervening variable. This research is an explanatory study. The population in this study were employees of each village apparatus. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, showed that Leadership Style has a significant positive effect on Work Motivation, Work Environment has a significant positive effect on Work Motivation, Work Discipline has a significant positive effect on Work Motivation, Leadership Style has a significant positive effect on Work Satisfaction, Work Environment has a positive but not significant effect on Work Satisfaction, Work Discipline has a positive but not significant effect on Work Satisfaction, Work Motivation has a significant positive effect on Work Satisfaction. The results of the indirect influence hypothesis test show that the variables of Leadership style on Job satisfaction through Work motivation have a significant positive effect, Work environment on Job satisfaction through Work motivation has a significant positive effect, Work discipline on Job satisfaction through Work motivation has a significant positive effect.